Perbandingan Hasil Belajar Biologi Dengan Menggunakan Model Pembelajaran Kooperatif Script daN Model Pembelajaran Konvensional pada Pokok Bahasan Sistem Eskresi di Kelas VIII SMP Muhammadiyah 11 Tello Makassar - Muh. Putra N Rizaldi Trias Jaya Putra Nurdin (Universitas Islam Negeri Mataram, 2017)
In the world of education, improving the quality of learning both in the mastery of materials and learning methods are always strived. One of the efforts that teachers do in improving the quality of teachers is the preparation of various scenarios of learning activities in the classroom. This study aims to determine the comparison of biological learning outcomes by using cooperative learning model script and conventional learning model. This research was conducted at SMP Muhammadiyah 11 Tello Makassar in March until April 2016. The research method used was a Quasy Eksperiment. The research instrument used is the learning result instrument and tested through t-test statistic. The results obtained that t-count value for post-test data in the experimental class of 3.81 while t-table at the level of significance level α 5%, then the value of α designated in table t is 2.00, so obtained t count ≥ t table (3.81 ≥ 2.00 ). This study suggested that cooperative learning scripts can improve students learning outcomes. Keywords: Cooperative Learning script, Conventional Learning, Learning outcomes